Diuretic effects of Hecogenin and Hecogenin acetate via aldosterone synthase inhibition - Abdulmohsin J. Alamoudi; Maria Nazeer; Nabi Shah; Saif Ullah; Meshal Alshamrani; Waleed Y. Rizg; Osama M. Ashour; Ashraf B. Abdel-naim; Abdul Jabbar Shah (Elsevier, 2024)
Hecogenin (HEC) is a steroidal saponin found in many plant species and serves as a precursor for steroidal drugs. The diuretic effects of HEC and its derivative, hecogenin acetate (HA), remain largely unexplored. The present study aimed to explore the potential diuretic effects of HEC and HA compared to furosemide (FUR) and spironolactone (SPIR). Additionally, the study aimed to explore the underlying mechanism particularly focusing on aldosterone synthase gene expression. Fifty-four Sprague-Dawley rats were allocated into nine groups (Group 1-9). Group 1 (control) received the vehicle, Groups 2 received FUR 10 mg/kg, Group 3, 4, and 5 were given HEC, while Groups 6, 7 and 8 received HA i.p at doses of 5, 10, and 25 mg/kg, respectively. Group 9 received SPIR i.p at the dose of 25 mg/kg. Urine volume, diuretic index and diuretic activity were monitored at 1, 2, 3, 4, 5, 6, and 24 h post-administration. Treatment was given daily for seven days. After that, rats were sacrificed and blood was collected for serum electrolytes determination. Adrenal glands were dissected out for gene expression studies. The results revealed that HEC and HA at the administered doses significantly and dose-dependently increased urine and electrolyte excretion. These results were primarily observed at 25 mg/kg of each compound. Gene expression studies demonstrated a dose-dependent reduction in aldosterone synthase gene expression, suggesting aldosterone synthesis inhibition as a potential mechanism for their diuretic activity. Notably, HA exhibited more pronounced diuretic effects surpassing those of HEC. This enhanced diuretic activity of HA can be attributed to its stronger impact on aldosterone synthase inhibition. These findings offer valuable insights into the diuretic effects of both HEC and HA along with their underlying molecular mechanisms.